A multiresolution signaling scheme for frequency-hop systems - Conner, K.F.; Baum, C.W. (MILCOM 1996: Conference Proceedings, 1996)
The simultaneous transmission of correlated data streams over a single channel is of interest for communications involving multimedia applications. This paper presents a multiresolution signaling technique that employs a form of M-ary differential phase shift keying (MDPSK) within the context of a binary FSK frequency-hop system. The technique permits the addition of MDPSK modulation into existing BFSK systems without requiring replacement of existing receivers. Methods are given for incorporating Reed-Solomon error control coding, CRC error detection, and erasure generation with this scheme. Two coding/erasure configurations are analyzed and performance results are given for a frequency-hop system subject to partial-band interference.